PROBLEMS AND PROSPECTS OF THE UNORGANISED SECTOR IN KERALA: REFERENCE TO SALES WOMEN IN TEXTILES - Fathima Adeela Beevi (Abhinav National Monthly Refereed Journal of Research in Commerce & Management, 2014)
The unorganized women workers are living below the minimum accepted standards without adequate facilities and having very lower income that did not meet their daily needs of life. Unorganised women workers including home-based works likes rolling papad and beedis, self-employment programs likes selling vegetables, employment in household enterprises and small units, agricultural workers, labour on construction sites, domestic work, handicrafts, khadi and village industries, handloom weaving and sericulture etc. The more women workers were employed mainly in the field of textile sector as sales women and comparatively more opportunities are there. They worked hard in shops to make their life better and reach their children in quality education and healthy food without acquiring any special skill and training. The study focused on the job satisfaction of sales women and the data were collected from 85 respondents and also from various books, reports, journals and websites. This is revealed that most of the women were satisfied with the facilities at work place given by the employer like special refreshment room for the women staff and staying or hostel facility etc but there is no time for refreshment because of continuous working hours without shifting and seasonal workload